New parallel stimulation strategies revisited: Effect of synchronous multi electrode stimulation on rate discrimination in cochlear implant users. - Bahmer, Andreas; Baumann, Uwe (Cochlear Implants International: An Interdisciplinary Journal, 2013)
Objectives Most cochlear implants implement stimulation strategies which apply sequential electrical pulses to encode acoustic signals such as speech, noise, and sounds via electrical stimulation of the auditory nerve. Parallel stimulation of adjacent electrodes has been employed in recent cochlear implant (CI) systems in an endeavor to improve coding of pitch information (e.g. FS4-p fine structure with parallel signal processing MED-EL, Innsbruck, Austria; VCIS, AB Corp., Sylmar, CA, USA). We investigated whether parallel stimulation of three adjacent electrodes enhances rate pitch perception compared with single electrode stimulation. Methods Most comfortable loudness (MCLs) levels were assessed in single and multi electrode condition in 12 subjects (15 ears, PULSARci100/SONATAti100 implant, MED-EL). Rate pitch discrimination was determined by means of an adaptive procedure (two-interval two-alternative forced choice, 2I2AFC) at individual MCL in the single- and multi-electrode condition at base frequencies of 100, 200, 283, 400, and 566 pulses per second (pps) (single electrode condition: electrode 5, multi electrode condition: electrode 4, 5, 6; PULSARci100/SONATAti100 implant: 12 electrode contacts; 1, most apical; 12, most basal). Results To achieve MCL in the multi-electrode condition significantly higher stimulation current compared with single stimulation was required. No significant difference between single- and multi-electrode condition just noticeable differences in rate discrimination (JNDR) group was found. In contrast, a pairwise comparison of individual results in a subgroup recruited out of successfully completed runs at high base rates showed statistically an improved rate discrimination in 17 of 24 runs in the multi-electrode condition. Therefore, a potential effect of parallel stimulation on rate discrimination is conceivable. Discussion The results in a subgroup of this study indicate that, compared with single-electrode stimulation, synchronous multi-electrode stimulation of three adjacent electrodes shows improvement rate discrimination in 17 of 24 test runs (binomial and [chi](2) test, P = 0.05) but did not result in statistically better JNDRs (best averaged improvement 19.8% at base rate 400 pps).